1999
DOI: 10.1039/a902990g
|View full text |Cite
|
Sign up to set email alerts
|

Catalytically self-threading polyrotaxanes

Abstract: A mainchain polyrotaxane is formed in which polymerisation and rotaxane formation occur simultaneously, due to the presence of the catalytically-active self-threading macrocycle cucurbituril.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
82
0
3

Year Published

2000
2000
2011
2011

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 126 publications
(85 citation statements)
references
References 15 publications
0
82
0
3
Order By: Relevance
“…This type of catalysis is reminiscent of the cyclooctyne ring-strain strategy in that the inclusion of the azide and alkyne inside the cavity of CB creates a geometry similar to that of the transition state, and hence, speeds up the reaction dramatically. In 1999, the Steinke group [26] exploited this catalysis to synthesize polyrotaxanes. In the context of using electron-deficient alkynes, as early as 1996 our own group [27] has employed the use of the bulky symmetric di-tert-butyl acetylenedicarboxylate to participate in a copper-free 1,3-dipolar cycloaddition, with the steric bulk associated with the triazole ring serving as a stopper.…”
Section: 3-dipolar Cycloadditions Of Azides With Alkynesmentioning
confidence: 99%
“…This type of catalysis is reminiscent of the cyclooctyne ring-strain strategy in that the inclusion of the azide and alkyne inside the cavity of CB creates a geometry similar to that of the transition state, and hence, speeds up the reaction dramatically. In 1999, the Steinke group [26] exploited this catalysis to synthesize polyrotaxanes. In the context of using electron-deficient alkynes, as early as 1996 our own group [27] has employed the use of the bulky symmetric di-tert-butyl acetylenedicarboxylate to participate in a copper-free 1,3-dipolar cycloaddition, with the steric bulk associated with the triazole ring serving as a stopper.…”
Section: 3-dipolar Cycloadditions Of Azides With Alkynesmentioning
confidence: 99%
“…In more recent work, Tuncel and Steinke have shown that this cucurbituril-catalyzed Diels-Alder reaction can also be applied in the synthesis of polyrotaxanes by using diazides and diacetylenes as the substrates. 55,56 The octameric analogue cucurbit [8]uril, which has a cavity with a size comparable to that of γ-CD, can accommodate two aromatic guest molecules. The cavity was used as a nanoreactor in the [2+2]-photodimerization of (E)-diammoniumstilbene in aqueous solution.…”
Section: Covalent Systemsmentioning
confidence: 99%
“…We know from our previous work that the nature of the spacer (i.e., shape, size, and length) affects the catalytic ability of CB6 during [3 + 2] cycloaddition reactions. [8][9][10] Therefore, one should carefully choose a spacer that has a lower affinity constant for CB6 than prop-2-ynylamine or azidoethylamine. It is known from the literature that CB6 can form fairly stable host-guest complexes with diaminoalkanes if the number of methylene units in the spacer is between three and eight.…”
Section: Resultsmentioning
confidence: 99%
“…Cucurbiturils have a hydrophobic cavity and two identical hydrophilic carbonyl portals. [6][7][8][9][10][11][12][13] CB6 binds well to protonated mono-and diaminoalkanes as a result of these structural features, mainly through ion-dipole interactions and the hydrophobic effect.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation